IMPLEMENTASI IOT NODE MCU DALAM PENGENDALI BEBAN LISTRIK RUMAH TINGGAL - Mesdi, Mesdi; Aryza, Solly; Wibowo, Pristisal; Anisah, Siti; Hamdani, Hamdani (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
This research discusses the electrical load controllers of the house that implements the latest system with the IOT method which replaces the general controls that activate / deactivate it near the electric load, so that a controller system design that can be controlled anywhere is made. By utilizing NodeMCU E3SP 8266 technology and Android as the control center and the internet / WIFI network as the connection media. The test results of this tool can be controlled / controlled anywhere while still connected to the internet / WIFI network.